2018
DOI: 10.1371/journal.pone.0206353
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and related factors of Active and Healthy Ageing in Europe according to two models: Results from the Survey of Health, Ageing and Retirement in Europe (SHARE)

Abstract: BackgroundActive and Healthy Ageing (AHA) is the process of optimizing opportunities related to health, participation, and safety in order to improve quality of life. The approach most often used to measure AHA is Rowe and Kahn’s Satisfactory Ageing model. Nonetheless, this model has limitations. One of the strategic objectives of the WHO Global Strategy and Action Plan (2016) is to improve Healthy Ageing measurement. Our objectives were to compare two models of assessing AHA and further compare the results by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 62 publications
3
49
2
4
Order By: Relevance
“…Compared with the rest of China, the SA prevalence in the present study was similar to that reported in Taiwan (26.5%), 12 higher than that in Hong Kong (0.7~33.1%) and lower than that in Shanghai (46.2%) . When compared with the rest of the world, these rates were higher than those reported in Brazil (25%) and in Europe (23.5%) . This discrepancy is likely related to different regions and economic levels.…”
Section: Discussionsupporting
confidence: 72%
“…Compared with the rest of China, the SA prevalence in the present study was similar to that reported in Taiwan (26.5%), 12 higher than that in Hong Kong (0.7~33.1%) and lower than that in Shanghai (46.2%) . When compared with the rest of the world, these rates were higher than those reported in Brazil (25%) and in Europe (23.5%) . This discrepancy is likely related to different regions and economic levels.…”
Section: Discussionsupporting
confidence: 72%
“…For the EU-15 countries, the focus has to be on the following policy interventions: A rethinking of passive labor market policies in order to sustain the 55-65-year-old working group, but also to target increases of active labor market policies for this age cohort; keeping up the R&D expenditure, oriented toward labor skills of the 55-64-year-old working group; reconsideration of EDU for 55-64-year-olds, levels 3-8, oriented towards migrants' inclusion in educational programs (since, in these countries, there is a large flow of migrants from developing countries) [73], and also to 55-64-year-olds for native working people by reshaping their skills as requirements are transformed by the emergence of new digital technologies [68,74]; oriented hospital services to boost healthy conditions and perceptions of people, and thus, making them confident in the public health expenditure in the case of child birth and care, therefore indirectly sustaining birth rates and life expectancy; further government health expenditure aimed at tackling the population aging phenomenon correlated with increasing long-term healthcare in the case of the elderly; and promoting and supporting preventive health actions among people aged 55-64 and low-and medium-educated people, since these categories are the most distant from health prevention, as Bremer et al [27] demonstrated. Under these cumulative interventions, labor productivity within developed EU MS will increase, with direct effects on wellbeing and overall economic development [10,20,[35][36][37][38].…”
Section: Results Of the Structural Equation Model (Sem)mentioning
confidence: 99%
“…When examining how this phenomenon influences policies within the EU-28 MS, it becomes obvious that, as some researchers have pointed out, "gloom and doom" predictions are frequently misplaced, and population aging does not present as heavy a social and economic burden as once considered [19,33,34]. On the contrary, aging populations have favorable impacts on labor productivity, as evidenced in multiple studies [10,20,[35][36][37][38]. Aging generates increases in the needs of old cohorts that are not as high as originally thought, and older individuals in good health tend to contribute long after retiring by providing compensated and uncompensated labor.…”
Section: Health Aging and Welfare/labor Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…HA is equated to life quality, which is relevantly determined by emotional, social and financial factors. Therefore, HA is mainly conditioned by the physical and emotional health, as well as by social aspects, encompassing a multidimensional perspective of the concept of health [ 45 ]. It is worth mentioning that, in 2018, the number of healthy life years at birth was estimated at 64.2 years for women and 63.7 years for men [ 46 ], while the life expectancy at birth in Europe for the same year was 81.0 years (78.3 years for men and 83.6 years for women) [ 47 ].…”
Section: Discussionmentioning
confidence: 99%